SUBALTERNITY ISSUES IN STEVE MCQUEEN’S MOVIE 12-YEARS A SLAVE - Felia Aditya S. Meliala; Mike Wijaya Saragih (Prodi Sastra Inggris UKI, 2020)
This paper aims to show the form of subalternity which occurs in the movie 12 Years a Slave (2013), a biopic of a slave and his life in the times of racism and slaves in America in the year 1841. Being a black person during that time was extremely difficult as they were treated as slaves and were sold freely and legally. This movie depicts the life of Solomon Northup, a kidnapped black freeman who was then sold as a slave to pick cotton. With slavery as its background, this movie shows a lot of graphic torture scenes which depict the cruelty with which white people tortured black people. To find the subalternity experienced by Solomon, the author will analyze the movie’s narrative and cinematography. Furthermore, this research will be based on Gayatri Spivak’s (1985) theory which discusses the voiceless and oppressed groups. The result of this research shows that in the movie 12 Years a Slave, subalternity is constantly found in Solomon’s life. Subalternity is reflected through Solomon’s experience as a part of the oppressed group whose lives are controlled by white people (the oppressor), whose voices are absent and who could only fight with hope and thoughts.